Improving Diagnostic and Therapeutic Measures in in Vitro Fertilization Cycles Based on Homocysteine Levels (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study explores the impact of homocysteine levels on infertility and IVF outcomes. A total of 50 patients with abnormal homocysteine levels underwent IVF after normalization, while 40 patients proceeded without prior testing. The results showed a significant improvement in antral follicle count (16.15±1.45 vs. 12.76±1.28, p